1991
DOI: 10.1111/j.1439-0450.1991.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA Fragments Coding for ST1 and LT1 Toxins, and K88 (F4) Adhesin in Enterotoxigenic Escherichia coli

Abstract: Ten porcine strains of enterotoxigenic Escherichja coli possessing the K88 (F4) adhesion fimbriae, were selected for study of enterotoxin-and fimbriae-encoding plasmids. Plasmid DNA, separated according to size by gel electrophoresis was transferred to nylon membranes by Southern blotting, and hybridized with enzyme-labelled oligonucleotide probes for STI and LTI enterotoxins, and a '*P-labelled probe for the F4 fimbriae. Plasmids possessing the enterotoxin genes ranged from 50 MDa to 78 MDa in size. The ST1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The most significant contributors to piglet ETEC diarrhea were LT and STb. The STb toxin gene has been primarily found in association with ETEC strains from scouring piglets (Erume et al 2008) and genes for LT and STb are usually found on the same plasmid (Wasteson and Olsvik 1991). Interestingly, a few Stx-2e toxin genes were present among E. coli isolates from diarrheic piglets without any clinical signs of edema disease.…”
Section: Discussionmentioning
confidence: 98%
“…The most significant contributors to piglet ETEC diarrhea were LT and STb. The STb toxin gene has been primarily found in association with ETEC strains from scouring piglets (Erume et al 2008) and genes for LT and STb are usually found on the same plasmid (Wasteson and Olsvik 1991). Interestingly, a few Stx-2e toxin genes were present among E. coli isolates from diarrheic piglets without any clinical signs of edema disease.…”
Section: Discussionmentioning
confidence: 98%
“…F4 synthesis is controlled by a non-conjugative plasmid [Shipley et al, 1978] with a ranging molecular weight of 50-177 MDa [Shipley et al, 1978;Wasteson and Olsvik, 1991;Bertin, 1992;de Graaf, 1990;Mainil et al, 1998]. Therefore, F4 expression by E. coli can be spontaneously lost [Ørskov and Ørskov, 1966].…”
Section: Genetic Organization Of the F4 Operonmentioning
confidence: 99%
“…According to their possession of distinct virulence genes, pathogenic E. coli strains are classified into several major categories, i.e., enterotoxigenic (ETEC), enteropathogenic (EPEC), enterohemorrhagic/shiga toxin producing E. coli (EHEC/STEC), enteroinvasive (EIEC), enteroaggregative (EAggEC) and the diffusely-adherent group (DAEC) [15,31]. In piglets, ETEC predominantly cause neonatal and postweaning diarrhea by producing heat-labile (LTh) and heat-stable (ST) enterotoxins [38,41]. LTh toxin shares 82% amino acid homology with cholera toxin, which leads to activation of adenyl cyclase and chloride ion efflux [19].…”
mentioning
confidence: 99%